Increasing students' physical activity during school physical education: rationale and protocol for the SELF-FIT cluster randomized controlled trial - Amy S. Ha; Chris Lonsdale; David R. Lubans; Johan Y. Y. Ng (BMC, 2017)
Abstract Background The Self-determined Exercise and Learning For FITness (SELF-FIT) is a multi-component school-based intervention based on tenets of self-determination theory. SELF-FIT aims to increase students' moderate-to-vigorous physical activity (MVPA) during physical education lessons, and enhance their autonomous motivation towards fitness activities. Using a cluster randomized controlled trial, we aim to examine the effects of the intervention on students' MVPA during school physical education. Methods Secondary 2 students (approximately aged 14 years) from 26 classes in 26 different schools will be recruited. After baseline assessments, students will be randomized into either the experimental group or wait-list control group using a matched-pair randomization. Teachers allocated to the experimental group will attend two half-day workshops and deliver the SELF-FIT intervention for 8 weeks. The main intervention components include training teachers to teach in more need supportive ways, and conducting fitness exercises using a fitness dice with interchangeable faces. Other motivational components, such as playing music during classes, are also included. The primary outcome of the trial is students' MVPA during PE lessons. Secondary outcomes include students' leisure-time MVPA, perceived need support from teachers, need satisfaction, autonomous motivation towards physical education, intention to engage in physical activity, psychological well-being, and health-related fitness (cardiorespiratory and muscular fitness). Quantitative data will be analyzed using multilevel modeling approaches. Focus group interviews will also be conducted to assess students' perceptions of the intervention. Discussion The SELF-FIT intervention has been designed to improve students' health and well-being by using high-intensity activities in classes delivered by teachers who have been trained to be autonomy needs supportive. If successful, scalable interventions based on SELF-FIT could be applied in physical education at large. Trial registration The trial is registered at the Australia New Zealand Clinical Trial Registry (Trial ID: ACTRN12615000633583 ; date of registration: 18 June 2015).